Photonic crystal cavity-enhanced emission from silicon vacancy centers in polycrystalline diamond achieved without postfabrication fine-tuning. Issue 24 (15th June 2020) - Ondič, Lukáš; Varga, Marian; Fait, Jan; Hruška, Karel; Jurka, Vlastimil; Kromka, Alexander; Maňák, Jan; Kapusta, Peter; Nováková, Jaroslava
Abstract : Photonic crystal cavities made of polycrystalline diamond show more than 2.5-fold enhancement of the SiV centers zero-phonon line intensity via coupling to the cavity photonic mode. Abstract : Diamond optical centers have recently emerged as promising single-photon sources for quantum photonics. Particularly, negatively charged silicon vacancy (SiV − ) centers show great promise due to their narrow zero-phonon emission line present also at room temperature. However, due to fabrication tolerances it is challenging to prepare directly photonic structures with optical modes spectrally matching the emission of SiV − centers. To reach the spectral overlap, photonic structures must typically undergo complicated post-processing treatment. In this work, suspended photonic crystal cavities made of polycrystalline diamond are engineered and more than 2.5-fold enhancement of the SiV − center zero-phonon line intensity via coupling to the cavity photonic mode is demonstrated. The intrinsic non-homogeneous thickness of the diamond thin layer within the sample is taken as an advantage that enables reaching the spectral overlap between the emission from SiV − centers and the cavity modes without any post-processing. Even with lower optical quality compared to monocrystalline diamond, the fabricated photonic structures show comparable efficiency for intensity enhancement. Therefore, the results of this work may open up a promising route for the application of polycrystalline diamond in photonics.